(untitled) (Medico Legal Update, 2020)
Background: Chronic tonsillitis is chronic inflammation of the palatine tonsils which can be caused by the presence of free radicals that stimulate the formation of pro-inflammatory cytokines such as Tumor Necrosis Factor-? (TNF-?) and interleukin-6 (Il-6). Astaxanthin as an antioxidant and anti-inflammatory is thought to reduce levels of proinflammatory cytokines. Aim: To determine plasma levels of TNF-? and palatine tonsill smears in patients with chronic tonsillitis before and after administration of astaxanthin. Method: Research with clinical trial design. Thirty-one subjects who met the inclusion and exclusion criteria in the Ear, Nose, Throat, Head and Neck Surgery clinic in Wahidin Sudirohusodo Hospital and Network Hospital were given astaxanthin 4 mg/day for 14 days. Plasma TNF-? levels and palatine tonsile smears were examined before and after administration of astaxanthin. Data were analyzed using SPSS 25th version. The statistical tests used Paired-t test and Independent-t test. Results: Thirty-one subjects can be followed until the end of the study. Astaxanthin 4 mg per day for 14 days can reduce plasma TNF-? levels and palatine tonsil swab of patients with chronic tonsillitis (p <0.05), and there is no significant difference in TNF-? levels between plasma and palatine tonsil swab both before and after administration astaxanthin (p> 0.05). Conclusion: Astaxanthin can reduce plasma TNF-? levels and palatine tonsil swab in chronic tonsillitis patients.